REPLICATION OF COMPARATIVE METHODS FOR SINGLE DATABASE PERFORMANCE IN CENTOS OPERATION SYSTEM WITH MAXSCALE - Merinda Lestandy; Mochammad Arif Hidayatullah; Amrul Faruq; Machmud Effendy; Muhammad Irfan (UIN Ar-Raniry, 2020)
Processing data in an institution or organization has become an activity or routine for each meeting. In processing data, of course there are various kinds of problems, ranging from missing data, either because of an error in entering data or the result of a system failure. To overcome these problems, in an agency or company must have data backup, so as to create problems that occur in the data, the institution still has data backup. To call, another method of database replication is used. From the test results obtained data on the value of RTA (Round Trip Average) that is the time required for one time sending and receiving data from the replication database is 5426.22 ms and for compilation service diagrams a query attack occurs with a percentage of 29% in the database applications that produce 1774.45 ms results and for service diagrams at a query attack percentage of 29% a single database estimates the server down.